$(w,c)$-Almost Periodic Generalized Functions - Khalladi, Mohammed Taha; Kostić, Marko; Rahmani, Abdelkader; Velinov, Daniel (Sarajevo Journal of Mathematics, 2022)
The aim of this work is to introduce and study a new space of $\left( w,c\right) -$almost periodic generalized functions containing the $\left( w,c\right) -$ almost periodic functions, $\left( w,c\right) -$almost periodic Schwartz distributions, the algebra of periodic generalized functions, the space of Bloch-periodic generalized functions as well as the space of $\left( w,c\right) -$periodic generalized functions.